Non-monetary burdens of out-of-pocket costs incurred by patients and caregivers for medical care: a scoping review - Kristen Capogrossi Giombi; Sophia D’Angelo; Sydney Kirsch; Ella Shenkar (BMJ Open)
Background Patients and their caregivers incur significant financial burden from health care costs, but the financial burden often does not consider additional impacts from non-monetary burdens.Objectives Examine the extent to which non-monetary burdens have been investigated and identify the methods and instruments used to collect non-monetary burdens through a systematic scoping review.Methods Scoping review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis and Joanna Briggs Institute guidance for scoping reviews.Data sources PubMed, CINAHL, EconLit and Web of Science were searched from 1 January 2013 to 7 November 2023. The search identified 950 articles.Data extraction and synthesis A dual independent review of titles, abstracts and full texts was conducted for inclusion, and data were extracted using DistillerSR software; 166 articles met the inclusion criteria.Results The included studies suggest three overarching categories of non-monetary burdens: material, psychological or psychosocial and coping behaviour. Within each of these categories, the literature has identified subcategories of burdens that vary in the extent to which they have been studied. This review also identifies 29 instruments used to collect non-monetary burdens from patients and caregivers across the included studies, of which 19 were validated. Many of these instruments were used in a single study.Conclusions The findings help illustrate the gaps in the literature on non-monetary burdens for patients and caregivers and provide a starting point for further investigation of this topic as well as implications for policy. Future research may reference the instruments highlighted in this study to help develop new instruments for capturing non-monetary burdens to better reflect the patient and caregiver experiences with financial toxicity due to medical expenses. Collecting more comprehensive data will provide a better understanding of the range and the extent of the non-monetary burdens faced by patients and caregivers. It will also increase the evidence to support new or existing targeted programmes and policies to help patients and caregivers better cope with these non-monetary burdens.